Ultrasound-guided venous catheterization: A useful extension of the radiographer’s role in CT-imaging - Mehus, Andrea; Johansen, Ina Maria; Løvland, Kristin (Radiography Open, 2022)
Introduction: In CT examinations, contrast agents are administrated in order to increase the contrast between different tissues and improve visualization of pathology. Safe contrast injection requires access via a catheter inserted into a suitable peripheral vein that can endure contrast flow. Peripheral vein cannulation can be difficult to obtain. Veins can lie deep in the tissue, be thin, porous or otherwise challenging to cannulate. The study aimed to get an insight into radiographers’ experiences with use of ultrasound-guided peripheral venous catheterization (USGPVC), and how this has affected their perception of workflow when performing contrast-enhanced CT-examinations. Methods: Semi-structured, individual interviews were conducted with seven radiographers from three different hospitals in Norway, all with experience with USGPVC. An interview guide was designed based on case studies before and after access to USGPVC. Thematic analysis was used to categorize and analyze the data material. Results: The thematic analysis showed three main themes: 1) Lack of time related to the workload throughout the day, and how the radiographers experienced access to US-device affected this. 2) Practical application of the PVC admission and what opportunities USGPVC offers the radiographers. 3) Patient care, and how the radiographers experience the USGPVC affects the quality of their work. Conclusion: The informants experienced a positive change in workflow in the CT-laboratory after they gained access to an US-device. They experienced an increased sense of control, mastery and time efficiency and this resulted in improved patient flow and increased professional pride.